Arte e tecnologia in Corea del Sud: tre mostre per una prospettiva occidentale - Francesco Spampinato (Antropologia e Teatro)
This essay offers a comparison between contemporary art from South Korea and art from Western countries, through the solo exhibitions of three South Korean artists of different generations who address media and technological issues in their work: Nam June Paik, Lee Bul and Anicka Yi. The exhibitions surveyed, which sealed the importance of these artists on a global scale, are the following: Paik's Exposition of Music - Electronic Television at Galerie Parnass in Wuppertal, Germany, 1963; Bul's The Monsters Show at Le Consortium in Dijon, France, 2002; and Yi's Life Is Cheap at the Guggenheim Museum in New York, United States, 2017. Through the gaze of these South Korean artists, it is possible to better understand the parameters of technological thinking in the West in distinct eras: the information age, in this case the 1960s, the post-human and cyberpunk culture of the 1990s, and the more recent post-Internet turn of the 2010s. The three exhibitions highlight a range of relationships, resemblances, reciprocities and repercussions between Europe and the United States on the one hand and East Asia on the other, but also peculiarities and differences that denote different conceptions and degrees of impact of digital media and technologies in their respective countries. What emerges, indeed, is the need to move beyond the traditional limits of colonialist-minded forms of techno-orientalism in favor of new avenues of interpretation of a peculiar Eastern technological thought, such as, for example, the concept of “Cosmotechnics” recently elaborated by Yuk Hui.